The importance of witches and their significance in Shakespeare's play Macbeth - قاسم الظواهري (آداب الكوفة, 2011)
The researcher found through reading Macbeth - Shakespeare - that some semantic contents refer to the openness of this text to multiple readings. In four axes, he tried to discuss the role of witches semantically, and what is being raised about the return of their dialogues to other than Shakespeare, this is in the first topic. As for the second topic, it deals with how the work of these characters was employed in order to provide a convincing picture of the actors’ movement in the entire theatrical text, and the third topic discussed how the writer’s vast imagination affects drawing the imagination of the characters’ images and the actions of each character that serve the implementation of the idea of ​​witches, while the fourth topic was diagnosing repetitions And its implications in clarifying the general idea, to conclude the research with the results and conclusions.